A Conversation Analysis: The Use of Small-Talk - Isnaeni Wahab; Zul Astri; Novalia Tanasy; Nurul Fachrunnisa (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2021)
This research aimed to find out the topic and the function of small talk that was used by the students. The method of the research was qualitative descriptive. This research took place in the English Education of Graduate Program, State University of Makassar. The data collected through recording the interaction of small talk naturally by recording. The result showed that most of the topics discussed during the small talk were about the immediate situation of the talk. The topic of small talk can be either shift to the external situation such as the latest news, economics, hobbies, sports, movies or celebrities, and communicational situations. And from this research, the researcher found some topics like movies and asking for files. Besides that, the function of small talk specifically in class serves as an ice-breaking and silence-filling function.